2015
DOI: 10.1037/a0038868
|View full text |Cite
|
Sign up to set email alerts
|

Early-adolescents’ reading comprehension and the stability of the middle school classroom-language environment.

Abstract: This study examined teachers' language use across the school year in 6th grade urban middle-school classrooms (n = 24) and investigated the influence of this classroom-based linguistic input on the reading comprehension skills of the students (n = 851; 599 language minority learners and 252 English-only) in the participating classrooms. Analysis of speech transcripts revealed substantial variability in teachers' use of sophisticated vocabulary and total amount of talk and that individual teacher's language use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 51 publications
1
12
0
2
Order By: Relevance
“…For example, in a study with college students, Carrell (1983) found that prior knowledge predicted reading comprehension in college students who were ELs, but not in students who were monolingual. Although differences in reading development between students who are ELs and students who are monolingual have been postulated (Hedgcock & Atkinson, 1993; Riddle Buly & Valencia, 2002), little comparative analysis has been conducted to understand whether and how the role of the predictors in reading comprehension differ by language status (Gámez & Lesaux, 2015). Comparative analyses of reading comprehension by language status can advance our understanding in this area and may offer suggestions to improve reading instruction in ways that meet the needs of students who are ELs (Lesaux & Kieffer, 2010).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…For example, in a study with college students, Carrell (1983) found that prior knowledge predicted reading comprehension in college students who were ELs, but not in students who were monolingual. Although differences in reading development between students who are ELs and students who are monolingual have been postulated (Hedgcock & Atkinson, 1993; Riddle Buly & Valencia, 2002), little comparative analysis has been conducted to understand whether and how the role of the predictors in reading comprehension differ by language status (Gámez & Lesaux, 2015). Comparative analyses of reading comprehension by language status can advance our understanding in this area and may offer suggestions to improve reading instruction in ways that meet the needs of students who are ELs (Lesaux & Kieffer, 2010).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Despite this compelling existing evidence of the potential of teacher talk to support motivational components of word learning and calls in the literature for teacher language that promotes word consciousness to be more pervasive in teacherstudent interactions, few studies use teacher utterances as the unit of analysis for exploring the content of teachers' talk (Gámez & Lesaux, 2015;Snow & Dickinson, 1991) and none to investigate word consciousness. Critical for developing this field, and ultimately increasing students' dispositions toward learning new words, is an understanding of teachers' everyday language use that can promote students' word consciousness.…”
Section: Teacher Talk To Foster Word Consciousnessmentioning
confidence: 99%
“…20, MET, 2012. Other systems designed to study teachers' instructional practices, have reported a positive association between teachers' practices and students' language and reading achievement despite wide variation in CREATING OPPORTUNITIES TO LEARN FROM TEXT: COLT 5 content and purpose (e.g., Chiang, et al, 2017;Dwyer, et al, 2016;Gámez & Lesaux, 2015;Michener et al, 2018;Taylor et al, 2003). For example, the Measuring Effective Teaching project (MET, used three different systems, including the CLASS (Hamre et al, 2013), to study teachers' literacy instruction, all of which accounted for a small but significant amount of the variance in student achievement.…”
Section: Observations Of Literacy Instructionmentioning
confidence: 99%